Genetic Variants Associated With Subjective Cognitive Decline in Patients With Migraine - Yeh, Po-Kuan; Liang, Chih-Sung; Tsai, Chia-Lin; Lin, Yu-Kai; Lin, Guan-Yu; Tsai, Chia-Kuang; Tsai, Ming-Chen; Liu, Yi; Tai, Yueh-Ming; Hung, Kuo-Sheng; Yang, Fu-Chi (Frontiers in Aging Neuroscience, 2022)
The genetic association between subjective cognitive decline (SCD) and migraine comorbidity remains unclear. Furthermore, single nucleotide polymorphisms (SNP) associated with SCD have not been identified previously. Migraineurs were genotyped using an Affymetrix array. The correlation between different SNP variants in migraineurs with or without SCD and non-migraine controls was investigated. Migraineurs with or without SCD were further divided for the analysis of relevant SNP variants linked to migraine with aura (MA), migraine without aura (MoA), episodic migraine (EM), and chronic migraine (CM). Significant connectivity between SNPs and clinical indices in migraineurs and non-migraine controls with SCD were assessed by a multivariate regression analysis. The rs144191744 SNP was found in migraineurs (p=3.19E-08), EM (p=1.34E-07), and MoA (p=7.69E-07) with and without SCD. The T allele frequency for rs144191744 in TGFBR3 was 0.0054 and 0.0445 in migraineurs with and without SCD (odds ratio, 0.12), respectively. rs2352564, rs6089473 in CDH4, rs112400385 in ST18, rs4488224 and rs17111203 in ARHGAP29 SNPs were found respectively in non-migraineurs (p=4.85E-06, p=8.28E-06), MoA (p=3.13E-07), and CM subgroups (p=1.05E-07, 6.24E-07) with and without SCD. rs144191744 closely relates to SCD with the All-migraine group and the EM and MoA subgroups. A multivariate regression revealed that subjective memory complaints were significantly associated with migraine duration (years), body mass index, and education (years) in the All-migraine cohort despite hospital anxiety and depression scale scores and age (years) across both groups. rs144191744 in TGFBR3 was significantly associated with SCD in migraineurs, especially in the EM and MoA patient subgroups. Three and two SNPs were linked to SCD in migraineurs and healthy controls, respectively.